DEVELOPING THE SEPARATING MECHANIZATION SYSTEM FOR POTATO TUBERS IN LOCALLY DESIGNED & PRODUCED POTATO LIFTER - Arkan Mohammad Amin (Mesopotamia Journal of Agriculture)
The purpose of this research is to study the effect of introducing a new technique to the lifter used for root crops on the product through adopting a more efficient separation device than the conventional one. This was achieved by using a soil separation device provided with a rotating spiral cylinder as a prototype for separating device. The crop chosen for testing of this technique was potatoes as it is one of the most important and sensitive product to the mechanical effect. This technique was compared with one stage vibrating chain separation lifter (made by the national institution for farming machine production in Algeria, certified by PAM comp. type 1908 – 1/R). The data were subjected to the statistical analyses by using a Randomized Complete Block Design (RCBD) in factorial experiment with three replications. Results of analyses of variance showed a significant difference between the two separation devices of lifting machines in its effects on all the studied properties with better results obtained by the cylindrical lifter on the chain lifter for both locations (Clay soil & Loamy-Sandy Soil). & it recorded (74.13 , 68.66)% for undamaged tubers , (16.19 , 19.71)% slightly damaged tubers , (7.84 , 10.75)% sever damaged tubers & (0.86 , 1.09)% for quantitative loss for both locations respectively